Análise econômica e ambiental da implantação de um esquema de centro de distribuição urbano para Belo Horizonte - Vagner de Assis Correia (2011)
The urban freight transportation is a fundamental activity to development of big cities and also to support peoples way of life and to improve industrial and commercial activities. Although this importance, urban transportation brings adverse effects on environment such as elevated energetic consumption, noise, visual intrusion and pollutant emissions. In Brazil, researches in relation to urban distribution have increased their relevance due to accelerated urbanization process and population growth that are impacting, directly, the demand and complexity of this sector. This research shows a methodology to assess the economical and environmental impacts of an urban distribution center scheme (UDC) with support of facilities location and vehicle routing tools. This methodology was applied in Belo Horizonte city (MG), where was assessed the retailers adoption in relation to UDC and scenarios were proposed in order to show the current freight distribution structure and possible configurations due to implementation of studied initiative. In addition, economical and environmental assessments were performed, according to previously defined parameters, allowing investigate the potential impact of UDC in relation to negative externalities mitigation of urban freight and distribution costs for supply chain as well. This work used TRANSCAD software in order to solve location and routing problems according real data from citys road net. The results of this research indicated that the developed scheme may improve cargo distribution to actors involved in this activity, as society, carriers and retailers, decreasing pollutant emissions and fuel consumption besides reducing distribution costs to companies. This work contributed to show the potential results from UDC as an alternative to optimize logistics processes in Belo Horizonte city